Practice of Classroom White Space in the Reform of PAD Teaching in “Biogas Engineering” - Zhang, Zhiping; Li, Yameng (Journal of Research in Vocational Education, 2025)
As a core elective in the Energy and Power Engineering major, the “Biogas Engineering” course covers essential knowledge that undergraduate students are expected to master proficiently. Under the traditional lecture-based teaching model, the commonly used “teacher question-student answer” approach often leads to multiple inefficiencies and reduced instructional effectiveness. To address these issues, the PAD (Presentation-Assimilation- Discussion) model encourages bilateral interaction between teaching and learning, enhancing student initiative and creativity, improving educational outcomes, and alleviating the teaching burden. Simultaneously, the application of “intentional silence” in classroom instruction often yields benefits that surpass expectations. It stimulates intrinsic learning motivation, fosters creative thinking, and promotes independent student character. The combined use of the Bipartite Classroom model and intentional silence transforms the learning process into a dynamic and constructive exchange.